Location and position estimation of wireless devices - Nawawi, Luqman Hakim; Khalifa, Othman Omran; Abdul Rahman, Farah; Nasir, Haidawati (IEEE, 2019)
Wireless localization technologies are currently a hotspot research area due to increasing number of wireless device around the globe. The aim of this paper is to explore the current techniques of wireless devices and to propose a new method to locate the lost devices or finding hidden devices without depending on the GPS in complex environment. The steps of the proposed method, first, the reference node which is the base station will gather the data of users and other related nodes such as the distance of the target node using three methods, Radio Signal Strength Intensity (RSSI), Time of Arrival (TOA), and Time Difference of Arrival (TDOA). Then, the initial value of Taylor Series Expansion (TSE) is calculated using Maximum Livelihood Estimation (MLE). Lastly, the performance of the developed method is evaluated in terms of accuracy and precision and benchmarked with related work in the same field.